2023
DOI: 10.1097/icb.0000000000001251
|View full text |Cite
|
Sign up to set email alerts
|

Vogt–koyanagi–harada Disease-Like Uveitis in a Patient With Advanced Melanoma Treated by Sequential Administration of Nivolumab and Dabrafenib/Trametinib Therapy

Abstract: Purpose: To describe a case of bilateral Vogt-Koyanagi-Harada (VKH)-like uveitis during treatment with dabrafenib and trametinib and three months after discontinuation of nivolumab for malignant melanoma, and discuss the possible (synergistic) role(s) of mitogen-activated protein kinase (MAPK) inhibitors and immune checkpoint inhibitors in its pathophysiology.Methods: Retrospective case report with fluorescein angiography and optical coherence tomography.Results: A 55-year old patient with metastatic melanoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…A study of individual case safety reports from the WHO international pharmacovigilance database found that ICIs and protein kinase inhibitors were the only drugs associated with druginduced VKH-like uveitis [68]. Our literature search yielded 24 retrospective studies, case reports, and case series analyzing VKH-like uveitis in the context of ICI therapy, totalling 41 patients [68][69][70][100][101][102][103][134][135][136][137][138][139][140][141][142][143][144][145][146][147][148][149][150]. Details of the included study data are found in Appendix B (Table A4).…”
Section: Vogt-koyanagi-harada-like Uveitismentioning
confidence: 99%
“…A study of individual case safety reports from the WHO international pharmacovigilance database found that ICIs and protein kinase inhibitors were the only drugs associated with druginduced VKH-like uveitis [68]. Our literature search yielded 24 retrospective studies, case reports, and case series analyzing VKH-like uveitis in the context of ICI therapy, totalling 41 patients [68][69][70][100][101][102][103][134][135][136][137][138][139][140][141][142][143][144][145][146][147][148][149][150]. Details of the included study data are found in Appendix B (Table A4).…”
Section: Vogt-koyanagi-harada-like Uveitismentioning
confidence: 99%